Resiliensi Santri: Studi Internet Addiction pada Generasi Alpha - Subahri, Bambang; Said, Imam Ghazali (UIN Sunan Kalijaga, 2025)
This research examines the academic resilience of Alpha generation students who experience internet addiction, with a focus on the impact of digital technology on their psychological development in the Islamic boarding school environment. In addition, this study also seeks to understand the mechanism of students’ resilience in fighting the challenges of internet addiction, to support their personality development and achievement in the digital era. This study uses a qualitative case study approach to explore factors such as social support, coping skills, religiosity, and Islamic boarding school values ​​that offer solutions based on Islamic psychology to strengthen the mental resilience of students in the digital era. The conclusion of this study states that internet addiction among students has a significant impact on their ability to adapt to more discipline and limited access to technology in Islamic boarding school life. Dependence on the internet causes students to feel isolated, anxious, and frustrated which hinders their resilience in facing academic and social challenges in a new environment. However, Islamic Boarding Schools address this problem with character-building programs that emphasize discipline and responsibility and provide Islamic guidance and counselling services that help identify and overcome internet addiction, as well as alternative facilities such as sports. Arts are also offered to distract students from excessive internet use, support the development of interests and talents, and strengthen their academic resilience.Penelitian ini mengkaji resiliensi akademik santri generasi Alpha yang mengalami kecanduan internet, dengan fokus pada dampak teknologi digital terhadap perkembangan psikologis mereka di lingkungan pondok pesantren. Selain itu, penelitian ini juga berupaya memahami mekanisme resiliensi santri dalam menghadapi tantangan kecanduan internet, guna mendukung perkembangan kepribadian dan pencapaian prestasi mereka di era digital. Penelitian ini menggunakan pendekatan kualitatif studi kasus untuk mengeksplorasi faktor-faktor seperti dukungan sosial, keterampilan coping, religiusitas dan nilai kepesantrenan yang menawarkan solusi berbasis psikologi islam untuk memperkuat ketahanan mental. Kesimpulan dari penelitian ini menyatakan bahwa kecanduan internet di kalangan santri, menunjukkan dampak signifikan terhadap kemampuan mereka untuk beradaptasi dengan kehidupan pesantren yang lebih disiplin dan terbatas akses teknologi. Ketergantungan pada internet menyebabkan santri merasa terisolasi, cemas dan frustrasi yang menghambat resiliensi mereka dalam menghadapi tantangan akademik dan sosial di lingkungan yang baru. Namun demikian, Pondok Pesantren mengatasi masalah ini dengan program pembinaan karakter yang menekankan disiplin dan tanggung jawab, serta menyediakan layanan bimbingan dan konseling islam yang membantu mengidentifikasi serta mengatasi kecanduan internet, juga fasilitas alternatif seperti olahraga dan seni juga diberikan untuk mengalihkan perhatian santri dari penggunaan internet berlebihan, mendukung pengembangan minat dan bakat, serta memperkuat resiliensi akademik mereka.